Bone Marrow T Cells at the Center Stage in Immunological Memory - Francesca Di Rosa (Frontiers Research Topics, 2017)
Increasing evidence supports the notion that bone marrow (BM) represents a relevant player in T cell responses, particularly in its role as a specialized organ for long-term memory. Memory T cells are enriched in the BM over long times after priming, and can be recruited to the periphery upon antigenic challenge. The articles in this research topic include discussions of whether these T cells are passing-through or truly resident, as well as a debate on the extent of proliferation of BM memory T cells. Original research articles in this collection include an analysis of the number of memory T cells found in different bones as well as effects of B cell depletion on T cell memory in the BM. T cells in the BM can influence a number of processes, from bone remodeling, control of cancer, to effects on hemopoiesis or Graft versus Host Disease (GVHD). This research topic contains several contributions to these topics including discussions on how to translate BM T cell knowledge into medicine.